2016
DOI: 10.1159/000442939
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-Lymphocyte Ratio Improves the Predictive Power of GRACE Risk Score for Long-Term Cardiovascular Events in Patients with Acute Coronary Syndrome

Abstract: Objectives: This study aims to evaluate the relationship between platelet-to-lymphocyte ratio (PLR) and GRACE risk score and to examine whether PLR on admission can improve the predictive value of GRACE risk score for cardiovascular disease (CVD) events in patients with acute coronary syndrome (ACS). Methods: PLR was calculated from the platelet and lymphocyte counts from the complete blood count of 2,230 ACS patients upon admission. The GRACE risk score was also calculated. Results: Spearman's rank correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Zhou et al . showed a positive association between GRACE risk score and PLR8. The PLR was also reported to be significantly correlated with other inflammatory markers such as C-reactive protein (CRP) and fibrinogen, which have been demonstrated to have predictive and prognostic significance in cardiovascular diseases39.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Zhou et al . showed a positive association between GRACE risk score and PLR8. The PLR was also reported to be significantly correlated with other inflammatory markers such as C-reactive protein (CRP) and fibrinogen, which have been demonstrated to have predictive and prognostic significance in cardiovascular diseases39.…”
Section: Discussionmentioning
confidence: 96%
“…The inclusion criteria were listed as follows: (1) All patients were diagnosed as ACS, including acute ST elevation myocardial infarction, acute non-ST elevation myocardial infarction and unstable angina8. (2) Blood samples for PLR determination were taken at admission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Studies showed that higher values of PLR were associated with an increased occurrence of cardiovascular events in patients after ACS. 34,35 Of interest, the main predictor of long-term mortality was age, which is a constant finding. 36 The second predictor of mortality was the type of the used P2Y12 inhibitor underlining its importance even with regard to long-term outcomes.…”
Section: Patients With Diabetes Under Clopidogrel Treatment Dis-mentioning
confidence: 99%
“…Chronic inflammatory processes are related to the pathogenesis and extension of atherosclerosis in coronary artery disease. [ 7 ] Several studies show that inflammatory markers, such as C-reactive protein (CRP), [ 8 , 9 ] neutrophil counts, [ 10 ] mean platelet volume, [ 11 ] platelet-to-lymphocyte ratio, [ 12 ] and neutrophil-to-lymphocyte ratio, [ 13 , 14 ] correlate with GRS and adversely predict short- and long-term prognosis. However, none of these works demonstrates the independent predictive value of the erythrocyte sedimentation rate (ESR) on clinical adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%